Eurocentrism in Samuel P. Huntington’s Concept of the Clash of Civilisations - Mateusz Kufliński (Polish Political Science Yearbook, 2022)
The article is dedicated to an issue of Eurocentrism in American political scientist Samuel P. Huntington’s concept of the clash of civilisations. The arguments presented indicate that Huntington’s concept is pure Eurocentric. I start by mentioning a few of Huntington’s critics (Noam Chomsky, Samir Amin, Arjun Appadurai, and John M. Hobson). The next step includes analysing in detail the “Eurocentrism anatomy” and presenting Eurocentrism as a phenomenon based on two axes, which I call “materialistic” and “epistemological”. In other words, Eurocentrism is a kind of spectrum. Thanks to that, I compare Huntington’s concept with facts from literature embedded in both axes. Apart from other arguments, Eurocentric factors in the clash of civilisations are 1) civilisations in the past, 2) origin of the West, 3) demographic argument, and 4) the downfall of the West. I argue that the clash of civilisations is based on false, Eurocentric assumptions and prejudices.